EDUCAȚIA ONLINE ÎN CONTEXTUL PANDEMIEI DE COVID 19 – ÎNTRE FORME DE DISCRIMINARE ȘI VARIANTE VIABILE DE ÎNVĂȚARE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
The Online Education in the Context of Covid -19 Pandemic – between Forms of Discrimination and Viable Ways of Learning.The Covid-19 Pandemic changed the way we live in ways we didn’t imagine. One of the biggest changes was the way education was shifted from the traditional face to face to online. For the teachers, students and families, this change came with many challenges, but it was seen as a necessary shift in the pandemic context. It was not the same though for the children coming from poor communities where there was no access to the internet or the necessary equipment to connect to the online platforms was not available. The experience of the online education in the context of Covid – 19 Pandemic can be used for a better approach in the way authorities and NGO’s support the students from disadvantaged communities.